Burden of Illness Associated with Peripheral and Central Neuropathic Pain among Adults Seeking Treatment in the United States: A Patient‐Centered Evaluation. Issue 12 (8th July 2014) - Schaefer, Caroline; Mann, Rachael; Sadosky, Alesia; Daniel, Shoshana; Parsons, Bruce; Nieshoff, Edward; Tuchman, Michael; Nalamachu, Srinivas; Anschel, Alan; Stacey, Brett R.
Abstract Objective The aim of this study was to evaluate patient‐reported burden associated with peripheral and central neuropathic pain (NeP) by pain severity and NeP condition. Design Six hundred twenty‐four subjects with one of six NeP conditions were recruited during routine office visits. Subjects consented to retrospective chart review and completed a one‐time questionnaire (including EuroQol‐5 dimensions, 12‐item Short‐Form Health Survey, Brief Pain Inventory‐Short Form, Medical Outcomes Study Sleep Scale, Hospital Anxiety and Depression Scale, and demographic and clinical characteristics). Pain severity scores were used to stratify subjects by mild, moderate, and severe pain. Summary statistics and frequency distributions were calculated. Differences by severity level were compared using Kruskal–Wallis (continuous variables) and chi‐square or Fisher's exact test (categorical variables). Effect size was computed with Cohen's d (mild vs severe). Results Subjects' mean age was 55.5. The majority (80.8%) had moderate or severe pain. Patient‐reported outcomes (health status, physical and mental health, pain interference with function, sleep, anxiety, and depression) were significantly worse among subjects with greater pain severity (all P < 0.0001). Severe pain subjects were negatively impacted by ≥30% in each outcome compared with mild pain subjects; standardized effect size was moderate for anxiety (0.59) and large (>0.95) for all others. The observed burden was most substantial among chronic low back pain‐NeP, although the pattern of disease burden was similar across the six NeP conditions. Conclusions Subjects across NeP conditions exhibited high pain levels, which were significantly associated with poor function, compromised health status and sleep, and increased anxiety and depression. Results indicate substantial patient burden across broad NeP, particularly among subjects with severe pain.